2014
DOI: 10.1016/j.celrep.2014.05.045
|View full text |Cite
|
Sign up to set email alerts
|

EZH2-Mediated Inactivation of IFN-γ-JAK-STAT1 Signaling Is an Effective Therapeutic Target in MYC-Driven Prostate Cancer

Abstract: Although small-molecule targeting of EZH2 appears to be effective in lymphomas carrying EZH2 activating mutations, finding similar approaches to target EZH2-overexpressing epithelial tumors remains challenging. In MYC-driven, but not PI3K-driven prostate cancer, we show that interferon-γ receptor 1 (IFNGR1) is directly repressed by EZH2 in a MYC-dependent manner and is downregulated in a subset of metastatic prostate cancers. EZH2 knockdown restored the expression of IFNGR1 and, when combined with IFN-γ treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 52 publications
7
83
1
Order By: Relevance
“…Its anticancer activity has been demonstrated in in vitro and in vivo in broad-spectrum cancer types, including lung, kidney, leukemia and prostate (Fillmore et al, 2015;Fiskus et al, 2009;Kikuchi et al, 2012;Liu et al, 2014;Wee et al, 2014). Although more specific EZH2 inhibitors (e.g.…”
Section: -Deazaneplanocin a (Dznep)mentioning
confidence: 99%
“…Its anticancer activity has been demonstrated in in vitro and in vivo in broad-spectrum cancer types, including lung, kidney, leukemia and prostate (Fillmore et al, 2015;Fiskus et al, 2009;Kikuchi et al, 2012;Liu et al, 2014;Wee et al, 2014). Although more specific EZH2 inhibitors (e.g.…”
Section: -Deazaneplanocin a (Dznep)mentioning
confidence: 99%
“…Data obtained in vitro in breast cancer showed that EZH2 specifically induces cell death in cancer cells but not in normal cells [83] . Moreover, in vivo studies showed that, treatments with some EZH2 inhibitors alone or in combination with other chemotherapeutic agents are well tolerated by mice resulting in minimal toxicity or modest weight loss of 10% [105,117,118] . Nevertheless, the studies described above demonstrated that EZH2 activity can behave differently in distinguishing neoplasms, and a singular inhibitor can be effective in certain kind of cancer but not in others.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, EZH2 catalytic inhibitors, although they efficiently reduced H3K27me3, failed to mimic EZH2 depletion. Therefore, patients with advanced prostate cancer driven by Myc could have benefits from a therapeutic depletion of EZH2, indicating that the ability of EZH2 to increase the sensitivity of cancer cells to interferon-γ is independent by its catalytic activity [118] . An important point for consideration, in order to understand if a drug is suitable for therapy, concerns taking into account its penetration into the organs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, a recent study showed that although inhibitors of EZH2, such as GSK126, have robust activity in the depletion of H3K27me3 in epithelial tumors cells, they have little effect on cancer cell growth. [9] Moreover, a peptide that induces the depletion of EZH2 protein complex is sufficient to inhibit cell growth. [10] This raises a possibility that targeting the EZH2 complex, rather than inhibiting H3K27me3, is required for blocking the EZH2-mediated oncogenic effect.…”
Section: Introductionmentioning
confidence: 99%